Penanaman Nilai-Nilai Kedisiplinan Melalui Peraturan Baris-Berbaris - Santosa, Prasetya Sigit; Dekanawati, Vivid; Ningrum Astriawati; Setiyantara, Yudhi; Subekti, Joko; Ekorius, Yunus; Setiawan, Dandi Alan (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
The Marching Line Regulation is an extracurricular activity to foster a sense of unity, responsibility and discipline in carrying out orders appropriately and quickly. The purpose of this community service is to instil the values of the discipline of student council members at Budi Utama Junior High School Yogyakarta against the rules and orders in the activities of the Marching Row Regulation. The method is used through the direct practice of Line-Marching. The process of instilling disciplinary values applied in UN activities is in the form of accuracy, obedience and compliance. The results of the assessment evaluation showed that the average assessment of the cultivation of disciplinary values obtained excellent criteria of 83% and good by 17%. The average results indicate the success of the implementation of training in the context of this community service.